1C.004 Epidemiology of fatal home injuries in rural Bangladesh. (14th March 2021) - Salam, Shumona; Hasan, Mehedi; Rahman, Qazi Sadeq-ur; Islam, Irteja; Arifeen, Shams El
Abstract : Background: The home is the most common location for fatal injuries in Bangladesh with 60% of deaths occurring in and around the home. This paper describes the epidemiology of fatal home injuries in rural Bangladesh Methods: A census and baseline survey was conducted as part of the Saving of Lives from Drowning (SoLiD) project in 7 purposively sampled rural sub-districts of Bangladesh. Information on socio-demographic characteristics, injury mortality and morbidity were collected from 1.2 million people between June and November, 2013. Descriptive analyses were done to quantify the burden of unintentional fatal home injuries. Results: 267 injury deaths were recorded over the 1-year recall period in the home environment (mortality rate was 23 [95% CI 20–26] per 100000 population per year). Leading causes of home injury deaths were drowning (53.7%), suicide (10.8%), falls (12.3%) and burns (9.3%). Children aged 1–4 years (97 [95% CI 78–120] per 100000) and adults older than 65 years (81 [95% CI 62–105] per 100000) were at high risk for injuries in the home (p<0.000). Drowning was the leading cause of death among children aged 1–9 years. Suicide followed by drowning was the main causes of deaths among adolescent males aged 10–14 years. Suicide followed by burn was the main cause of death among females aged 15–24 years. Falls was the main cause of death among adults older than 65 years. Recommendation: Interventions need to be promoted to ensure safer behaviours and help change home environments for families especially children in rural Bangladesh.